THE ROLE OF GYMNASTICS EXERCISES AS A FUNDAMENTAL FACTOR IN THE EDUCATION OF A HEALTHY GENERATION (The Conference Hub, 2025)
In the modern globalized society, the issue of raising a healthy generation has become one of the most pressing strategic priorities of national development policies. In this regard, physical education is not merely a subject but a multidimensional instrument that directly influences the physiological, psychological, cognitive, and social well-being of children and adolescents. Among the wide range of physical education methods, gymnastics exercises stand out as a scientifically grounded, cost-effective, and pedagogically flexible approach that simultaneously develops multiple motor skills, prevents postural deviations, enhances mental concentration, and lays the foundation for a physically resilient and intellectually capable young generation.